Adapting Social Safety Net Operations to Insecurity in the Sahel - Grun, Rebekka (World Bank, Washington, DC, 2020)
Adaptive Social Protection programs are increasingly implemented in fragile and insecure contexts in the Sahel. This paper provides a framework, key principles, and a repertoire of options for adapting social safety net projects to unprecedented levels of insecurity. It fills an operational knowledge gap regarding project design, implementation, and supervision under insecurity as called for by the World Bank Group’s strategy for fragility, conflict and violence 2020-2025. Based on a mix of desk research and field insights, the authors map operational security risks and identify ingredients for an appropriate response in risk assessment, design, beneficiary targeting, and payment systems.